Maizification of the landscape for biogas production? Identifying the likelihood of silage maize for biogas in Brandenburg from 2008-2018 - Felipe Vergara; Tobia Maike Lakes (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2019)
The development of biogas production in Germany has reshaped agricultural land use and production schemes since the implementation of the Renewable Energy Sources Act in 2000. It is associated with a widespread introduction of silage maize as a major substrate. While it contributes significantly to the renewable energy production, intensive maize-for-biogas production comes at the expense of loss of area for food production, is associated with negative ecological effects due to intensive and large-area monoculture, and is also associated with an increase in land prices. However, due to missing data, little is known about the plot-based distribution and development of silage maize for biogas production and, therefore, the local effects remain largely unstudied. This paper aims to identify the plot-level based likelihood of silage maize cultivated for biogas production in the Brandenburg region of Germany from 2008 through 2018. For this ongoing study, we developed and applied a spatially explicit multicriteria approach using plot-level land use information from Integrated Administration and Control System (IACS) data and additional datasets on biogas plants. Our initial results show that within the 10 years of this study, the area which was most likely used for biogas silage maize production has tripled. We also find biogas silage maize production has been concentrated in the northwest and central-east of the region, and we identified distinct silage maize hotspots within the area. To the knowledge of the authors, this is the first attempt at biogas production. From our study, we can derive some of the spatially explicit effects of the Renewable Energy Sources Act on local land use dynamics over time. This may be an important asset for comparative and future studies on the effects of policy-driven land use changes on ecological and land price outcomes which will be subject of further analyses.
Keywords: Q24; Q28; 330; Biogas; biogas silage maize; maizification; multicriteria approach; AHP; IACS; land use